# y`-xy^2=2xy ??

### 2 Answers | Add Yours

Since the request of the problem is vague, you may consider to solve the given equation such that:

`y - xy^2 = 2xy`

You need to factor out y to the left side such that:

`y(1-xy) = 2xy => y(1-xy)-2xy = 0 `

Factoring out y yields:

`y(1 - xy - 2x) = 0`

Setting each factor equal to zero such that:

`y = 0`

`1 - xy - 2x = 0 => -2x - xy = -1 => 2x + xy = 1`

You need to factor out x such that:

`x(2 + y) = 1`

Considering y=0 yields:

`2x = 1 => x = 1/2`

**Hence, evaluating x and y under the given conditions yields x`= 1/2` and `y = 0` .**

y-xy^2 = 2xy

y(1-xy) = 2xy

y not equla zero,

divide both side by y.

1-xy = 2x

add xy to both sides.

1-xy+xy = 2x+xy

xy + 2x = 1

x(y+2) = 1

x = 1 and y+2 =1

x = 1 and y = -1